Small-scale manjuba fishery around Cardoso Island State Park, SP, Brazil - Cardoso,T. A. (2006)
This work was carried out in the Enseada da Baleia and Vila Rápida communities. Data was provided by the Co-Management Committee of the Cardoso Island State Park (PEIC) on manjuba fishery management, technique and strategies used by the fishermen, as well as locally accumulated knowledge. Based on the results, social, ecological, and economic aspects of this type of fishing were analyzed. The importance of the accumulated knowledge and experience of this community, as well as the limitations imposed by local fishing gear, was concluded to be essential in conserving manjuba fishery conditions in the area. Industrial fishing, relevant state legislation, and market conditions were found to be the main obstacles to local fishery. Various proposals are suggested for manjuba fishery management, with emphasis on the need for fishing community participation in whatever measures are ultimately implemented.